2019
DOI: 10.1038/s41598-019-52798-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors related to anemia among Japanese adult women: Secondary data analysis using health check-up database

Abstract: The issue of anemia is important in terms of a woman’s preconception health. This study aimed to conduct an exploratory investigation of the prevalence of and factors related to anemia in non-pregnant Japanese women. Secondary data analysis was conducted using a database of women aged 20–49 years old who had attended an annual health check-up at a hospital in Tokyo (n = 10,598). A multiple logistic regression analysis was performed to identify factors related to anemia in two age groups: women aged 34 and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
3
22
1
1
Order By: Relevance
“…Our study found that past or current smokers decreased the risk of anemia, and current smokers were more likely to increase Hb and Hct levels. Similarly, the previous studies showed that smoking was negatively correlated with the risk of anemia [26][27][28]. The multiple logistic regression analysis from the health check-up database of St. Luke's international hospital in Tokyo, between April 2016 and March 2017, revealed that Japanese women (35-49 years) who were past or current smokers decreased the risk of anemia by 33% (OR = 0.67, 95% CI 0.56, 0.81, p < 0.001) or 25% (OR = 0.75, 95% CI 0.56, 0.99, p = 0.045), respectively, compared to those who were non-smokers, after adjusting for the covariates [26].…”
Section: Lifestyle and Anemiasupporting
confidence: 58%
See 2 more Smart Citations
“…Our study found that past or current smokers decreased the risk of anemia, and current smokers were more likely to increase Hb and Hct levels. Similarly, the previous studies showed that smoking was negatively correlated with the risk of anemia [26][27][28]. The multiple logistic regression analysis from the health check-up database of St. Luke's international hospital in Tokyo, between April 2016 and March 2017, revealed that Japanese women (35-49 years) who were past or current smokers decreased the risk of anemia by 33% (OR = 0.67, 95% CI 0.56, 0.81, p < 0.001) or 25% (OR = 0.75, 95% CI 0.56, 0.99, p = 0.045), respectively, compared to those who were non-smokers, after adjusting for the covariates [26].…”
Section: Lifestyle and Anemiasupporting
confidence: 58%
“…Our study observed that being overweight, obese, and having central obesity were correlated with increased odds of anemia, as well as decreased Hb, Hct, and RBC levels but increased WBC and CRP levels. However, the previous study showed that overweight Japanese women (BMI: 25.0-29.9 kg/m 2 ) aged 35-49 years were more likely to have a reduced risk of anemia (OR = 0.74, 95% CI 0.59, 0.92, p = 0.007) compared to those with normal BMI (18.5-24.9 kg/m 2 ); there was no significant association between obesity and anemia [26].…”
Section: Anthropometric Data and Anemiamentioning
confidence: 93%
See 1 more Smart Citation
“…Anemia is one of the common and major public health and nutritional problems globally [ 1 – 3 ]. The World Health Organization (WHO) defines anemia as a condition in which the number of red blood cells (oxygen caring capacity) is not adequate to meet the body’s physiologic needs [ 1 , 2 , 4 ]. Globally, anemia affects about two billion people, or one-third of the adult population lives [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wanita sangat rentan terhadap anemia karena mengalami menstruasi, kehamilan dan persalinan. Anemia didefinisikan sebagai kondisi di mana kadar hemoglobin (Hb) rendah dengan tingkat konsentrasi <12.0 g/dL sehingga tidak cukup untuk memenuhi kebutuhan fisiologis tubuh (Hisa et al, 2019).…”
Section: Pendahuluanunclassified